EVALUASI HAK & KEWAJIBAN ANTARA PERJANJIAN KONTRAK NASIONAL DENGAN PERSYARATAN STANDAR FIDIC (STUDI KASUS: PROYEK PEMBANGUNAN GEDUNG PEMUDA DAN KEBUDAYAAN TEMANGGUNG) - Satrio Agung Utomo; Yanuar Asmara Putra; Arif Hidayat; Frida Kistiani (Jurnal Karya Teknik Sipil, 2015)
In construction projects is often a dispute between the owner and the contractor, due to imbalance between the rights and obligations of the clauses of agreement contained in the contract agreement. Many standard contract used in Indonesia and abroad. One of the example is international FIDIC standard. To minimize imbalance, its important to know what are prone clause disputes based on standard FIDIC. The purpose of this study was to determine what clauses are prone to dispute and to see how the necessity of FIDIC standard is applied at the national contract documents. The data and information comes from the research and literature studies (books, regulations). Data processing is done by analyzing the rights and obligations of the owner and contractor clauses in contract document itself, then be reviewed with the FIDIC standard, and latter to compare the two. Regarding verification and validation perfomed by interviewing field of construction experts. The results showed that vulnerable disputed clauses are clause sanctions, payments, fines, bail enforcement, contract value, and the exercise period. Then concluded also that the terms of contract in Indonesia doesn’t need to refer FIDIC standard, because FIDIC standard deemed not appropriate when applied in Indonesia due to regulatory problems.